BHF and copula models in small area estimation for household per capita expenditure in Bogor District - BELINDA, NADIRA SRI; NOTODIPUTRO, KHAIRIL ANWAR; SOLEH, AGUS MOHAMAD (Jurnal Natural, 2024)
Small area statistics are required when the sample size is small to produce estimates with adequate precision. The assumptions underlying Battese Harter Fuller (BHF) unit-level models may often be unrealistic in some applications. Copula is an alternative approach when the assumptions are violated. This research discusses the performance of BHF and Copula in small area estimation (SAE) for estimating household per capita expenditure in sub-district levels. This study presents household per capita expenditure, which has a skewed distribution. Due to the fact that the data contains outliers, an appropriate method to handle outliers is also considered. In this research, the Gaussian and the Clayton Copulas are used. The results showed that the performance of BHF was better than Gaussian and Clayton Copulas, as indicated by small root mean square error (RMSE) with an average of 1.14, while the average RMSE of Gaussian copula was 2.71 and Clayton copula was 2.63. Furthermore, the coefficient of variation (CV) of BHF was also smaller compared to Gaussian and Clayton Copulas, and the resulting estimates can be categorized as reliable based on the CV of less than 25%.